James and the Giant Peach - Dahl, Roald; Blake, Quentin (New York : Puffin Books, an imprint of Penguin Random House LLC, 2016)
When a mysterious old man gives James some magical, tiny green things, he certainly never imagines that they will grow into an enormous peach.
790
Accelerated Reader
Keywords: Bugs; Fairy tales; Boys; Juvenile fiction; Peach; Juvenile fiction; Magic; Juvenile fiction; Insects; Juvenile Fiction; Aunts; Fiction; Friendship; Juvenile fiction; Boys; Fiction; Peach; Fiction; Magic; Fiction; Insects; Fiction; Friendship; Fiction; Boys -- Juvenile fiction; Magic -- Juvenile fiction; Insects -- Juvenile Fiction; Aunts -- Fiction; Friendship -- Juvenile fiction; Boys -- Fiction; Magic -- Fiction; Insects -- Fiction; Friendship -- Fiction; Peach -- Fiction; Boys -- Fiction; Peach -- Fiction; Magic; Fiction; Insects -- Fiction; Aunts -- Fiction; Friendship; Fiction; Magic; Fiction; Magic -- Fiction; Friendship; Fiction; Friendship -- Fiction; England; Juvenile fiction; England -- Juvenile fiction; England -- Fiction